Anterolateral congenital tibial bowing: case report - Mastantuoni, Giuseppe; Aulisa, Angelo Gabriele; Giordano, Marco; Savignoni, Pietro; Toniolo, Renato Maria; Falciglia, Francesco (Frontiers in Pediatrics, 2023)
Background The treatment of congenital curvatures (bowing) of the tibia still represents a challenging problem for all pediatric orthopedic surgeons because of its unpredictable course, especially if pseudoarthrosis occurs after a pathologic fracture of the tibia. Case presentation We describe the case of a child affected by an isolated curvature of his left leg. The congenital malformation was discovered at birth and no other pathological clinical finding was present. The first x-ray showed the presence of a congenital curvature of the tibia of the antero-lateral type. He was born in another country (Romania) and when he first came to our clinical observation at the Orthopedic and Traumatology Department, Pediatric Hospital “Bambino Gesu’”, Rome, the child was 14 months of age and had already started walking. Only a leg discrepancy of about 2 cm was present with consequent pelvis obliquity. At the beginning, we prescribed external lower limb orthoses and a simple shoe rise to prevent a tibial pathologic fracture and reduce pelvic obliquity. At periodical clinical follow-up visits and despite the external lower limb orthoses prescribed, a progressive worsening of the severe congenital tibial curvature was observed together with signs and symptoms, such as pain and limping, that suggested an objective “pre-fracture stage” of the tibial curvature; we decided to perform surgery. At the time of surgery, the child was three and a half years old. Surgery consisted of a double osteotomy, both of the fibula and of the tibia. Subtraction of the distal meta-diaphyseal portion of the fibula and tibial osteotomy in Correspondence: of the major anterolateral curvature. The tibial osteotomy was then stabilized by an internal Rush rod inserted proximally to the tibia under the cartilage growth plate and made it end inside the distal tibial epiphysis, crossing the distal tibial cartilage growth plate, preserving the ankle joint. Results The patient had an immediately excellent outcome. The tibial osteotomy site healed perfectly. At periodical orthopedic follow-up visits, the child was found to be always better. No clinical significative evidence of growth disturbances, due to the Rush rod that crossed the distal tibial cartilage growth plate, were noted. X-rays showed that the Rush rod progressively migrated with tibial growth together with the tibial bone growth, always getting further away from the distal tibial cartilage growth plate. Moreover, even the leg-length discrepancy and the pelvic obliquity improved. After an eight-year follow up, the patient, now a young boy of 11 and a half years, has an excellent outcome. Conclusions Our case report undoubtedly provides further important information for the treatment of these rare congenital disorders. In particular, it highlights the management of the “pre-fracture stage” in a severe congenital tibial antero-lateral curvature in a very young child and describes the surgical technique performed.